Improving Speaking Skill Through A Word-Guessing Game | La’batun Takhmin al-Kalimat fiy Kafaaty Maharatul al-Kalam: لعبة تخمين الكلمات في كفاءة مهارة الكلام - Uswatun Hasanah; Alda agus M (Mantiqu Tayr: Journal of Arabic Language, 2022)
In learning Arabic, interesting methods and teaching media are needed,in order the students can be motivated to learn actively. The word guessing game is kind of one interesting way to make the conditions comfortable education. As for the method used, it is part of cooperative learning, which is a word guessing game, and than In this research, the researcher chose the tittle improving speaking skill through A word-guessing game. The aim of this research is to find out whether the effect of guessing game on speaking skill. This study is used quantitative study with object 26 female students, and data collection was used by the test and linear regression analysis. Data collection technique using interviews and tests. The analysis used is linear regression. The result of the research that was conducted found that the word guessing game has a small effect in improving of speaking skill for the fourth year intensive female students at Al-Amien Islamic University.